دراسة لاعداد قائمة التدفقات النقدية في المصارف التججارية العراقية : بالتطبيق على مصرف الموصل للتنمية و الاستثمار - نادية سامي خضر (PROSPECTIVE RESEARCHES, 2023)
The economic unity has two aims to achieve, and equalize which are getting the most probable profit along and keep the liquidity of the economic unity. The success of the economic unity management to achieve the profits is measured by the income statement ,while the ability of economic unity to achieve the liquidity is measured by the data of the balance sheet which is limited and presents the nature of current assets and the current abilities as it benefits the users of financial statements to account the liquidity indicator and still dated with preparing the balance sheet, so to solve this problem the scientific society and professional institution recommend to prepare the statement of cash flows. The importance of this paper is to recognize the activity and aims of cash flows statements. Where as the aim of the paper is to measure the availability of cash flows statement in commercial Iraqi banks and the ability to prepare it .The problem of this paper is the lack of the financial statements in commercial bank to adopt the international standard (no.7) which is specific to prepare the cash flows statements as it obvious in its financial data. This paper adopts the hypothesis of preparing the cash flows statement in commercial bank to solve the problem, as it is considered the most important statement to explain the financial situation. The research depends on the characterized method through the concerned theses. This paper has arrived at certain recommendations and results.